Pro-inflammatory S100A9 contributes to retinal ganglion cell degeneration in glaucoma - Wang, Zuo; Chen, Yang; Wang, Jinxia; Xiu, Wenbo; Zhang, Gao; Gao, Yanping; Li, An; Long, Ping; Deng, Bolin; He, Chong; Lu, Fang (Frontiers in Immunology, 2025)
S100A9 is a pro-inflammatory protein involved in neuroinflammation and central nervous system (CNS) neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease. Glaucoma, the leading cause of irreversible blindness, shares common pathogenic mechanisms with CNS disorders. These parallels suggest a potential role for S100A9 in glaucoma; however, its precise contribution remains unclear. In this study, we investigated the association between S100A9 and glaucoma by enrolling 121 patients with glaucoma, administering intravitreal injections of recombinant murine S100A9 (rmS100A9), and employing an elevated intraocular pressure (EIOP)–induced glaucoma mouse model. We found that circulating S100A9 levels were elevated in patients with glaucoma and positively associated with disease stage. Retinal S100A9 expression was significantly elevated and correlated with progressive retinal ganglion cell (RGC) loss in EIOP glaucoma mice. Furthermore, intravitreal injection of rmS100A9 led to direct RGC degeneration. Both enrichment analyses and experimental validation indicated that S100A9 may contribute to glaucomatous injury by promoting neuroinflammatory responses in retinal microglia and astrocyte via activation of the Toll-like receptor 4 (TLR4) pathway. These results raise the possibility that S100A9 as a potential target for future therapeutic exploration in glaucoma.